The Relationship Between Plasma DPP4 Activity to BDNF Ratio and Mild Cognitive Impairment in Elderly Population With Normal Glucose Tolerance - Xiao, Liuping; Ge, Bo; Chen, Xu; Chen, Bo; Qin, Linyuan; Hu, Xueping; Pan, Haidong; Chen, Yujie; Tian, Li; Gao, Yun; Zheng, Tianpeng (Frontiers in Aging Neuroscience, 2019)
Objective: Since decreased brain-derived neurotrophic factor (BDNF) and increased dipeptidyl peptidase-4 (DPP4) activity have both been implicated in the pathogenesis of mild cognitive impairment (MCI), the aim of our study was to evaluate the association of MCI with plasma DPP4 activity to BDNF ratio (DBR) in elderly population with normal glucose tolerance. Methods: We cross-sectionally measured C-reactive protein, interleukin-6, nitrotyrosine, 8-iso-PGF2a, DPP4 activity, BDNF and calculated DBR in a total of 1,066 elderly participants in China. MCI was determined by Montreal Cognitive Assessment and finally confirmed by neurologists. Results: An inverse correlation was found between DPP4 activity and BDNF(r=-0.456, P<0.001) and this inverse correlation was partly mediated by nitrotyrosine and 8-iso-PGF2a. Across rising quartiles of DBR, nitrotyrosine, 8-iso-PGF2a, C-reactive protein and interleukin-6 progressively increased, whereas Montreal Cognitive Assessment score progressively decreased. Subjects in the lowest quartile of BDNF and highest quartiles of DBR and DPP4 activity had higher MCI risk compared with subjects in the highest quartile of BDNF and lowest quartiles of DBR and DPP4 activity, respectively (all P<0.05). The odds ratios for MCI became more pronounced with decreased BDNF and increased DPP4. Conclusion: In conclusion, a negative correlation was found between DPP4 activity and BDNF and this negative correlation was partly mediated by oxidative stress, not inflammation. DBR was positively associated with MCI and thus may be used as a novel risk biomarker for MCI in elderly population with normal glucose tolerance.